Identification of Striga hermonthica-Resistant Upland Rice Varieties in Sudan and Their Resistance Phenotypes - Samejima, Hiroaki; Babiker, Abdel G.; Mustafa, Ahmed; Sugimoto, Yukihiro (Frontiers in Plant Science, 2016)
Rice has become a major staple cereal in sub-Saharan Africa. Currently, upland rice cultivation is expanding particularly in rainfed areas where the root parasitic weed Striga hermonthica, a major constraint to cereal production, is endemic. Laboratory, pot, and semi-controlled open air experiments were performed to evaluate resistance of selected rice varieties in Sudan to a resident S. hermonthica population. In the laboratory, 27 varieties were screened for post-attachment resistance using the rhizotron technique. Varieties displaying high post-attachment resistance, Umgar, NERICA5, and NERICA13 together with NERICA4, NERICA18, and Nipponbare, a lowland rice variety, were further evaluated for performance and Striga resistance in pot and semi-controlled open air experiments and for germination inducing activity in a laboratory. In addition, comparative studies on reaction of Umgar, Kosti1 and Kosti2, released varieties for commercial production in Sudan, to the parasite were performed in two pot experiments. In the pot experiments Umgar and NERICA5, consistently, sustained the lowest Striga emergence (< 2.2 Striga plants per pot), while NERICA13 and NERICA4 supported 1.8–5.7 and 8.7–16.4 Striga plants per pot, respectively. In an artificially Striga-infested field, number of emergent Striga plants per 10 rice hills, at harvest, was 2.0, 2.0, 4.8, 13.5, 13.3, and 18.3 on Umgar, NERICA5, NERICA13, NERICA4, NERICA18, and Nipponbare, respectively. Striga had no adverse effects on total above-ground parts and panicle dry weight (DW) in Umgar and NERICA5. Germination-inducing activity of root exudates, at 14 days after sowing onwards, was markedly lower for Umgar than for NERICA5, NERICA13, NERICA4, and NERICA18. Based on these findings, Umgar has both pre and post-attachment resistance to a resident Striga population in Sudan. Kosti1 and Kosti2, did not exhibit Striga-resistance at the same level as Umgar. Further the resistance of NERICA5, a variety reported to be endowed with a broad spectrum resistance to Striga species and ecotypes, at least to one resident Striga population in Sudan was clearly indicated.